Advances in coupled use of renewable energy sources for performance enhancement of vapour compression heat pump: A systematic review of applications to buildings. (15th February 2023) - Cao, Jingyu; Zheng, Ling; Peng, Jinqing; Wang, Wenjie; Leung, Michael K.H.; Zheng, Zhanying; Hu, Mingke; Wang, Qiliang; Cai, Jingyong; Pei, Gang; Ji, Jie
Highlights: First reviews on coupling utilisation of thermal sources in vapour compression heat pumps. The existing thermal source coupling attempts in applied energy fields are summarised and compared. Design features and performance enhancement principles are analysed in detail. Recommendations for research and marketisation of energy source coupling methods are made. Abstract: Vapour compression heat pump provides efficient cooling and heating through the use of various renewable energy sources and plays a significant role in the energy conservation of modern buildings. Its performance enhancement gains increasing attention under the background of conventional energy and environmental crisis. Since the efficiency of a heat pump cycle is closely related to its thermal source condition, a stable high-temperature heat source or low-temperature cold source could benefit its heating or cooling efficiency a lot. Following this improvement strategy, significant progress has been made over the past years on the use of different renewable energy sources as coupled thermal sources of heat pumps. However, a specialised review that summarises relevant studies remains to be published. This paper aims at presenting operating mechanisms, characteristics, benefits, and limitations of different energy source coupling methods for heat pump performance enhancement towards its building application. The most concerning research on solar-assisted air source heat pumps, solar-assisted ground source heat pumps, and air-ground dual source heat pumps is emphasised. The existing thermal source coupling attempts under other renewable energy fields, such as waste heat, biomass, and water sources, are also summarised. Recommendations for further research and marketisation of such technologies are made based on detailed performance characterisation and comparison. The review is expected to benefit researchers in heat pumps and relevant applied energy fields to understand the challenges and opportunities in thermal source coupling technology and to promote its research and application development.